KESEJAHTERAAN PENGRAJIN GERABAH : PERSEPSI KEPATUHAN WAJIB PAJAK DI DESA WISATA KASONGAN - Rakhmadanni, Redya Elfryna; Rochmad Bayu Utomo (Accounting Department, Politeknik Negeri Bandung, 2025)
This study analyzes the extent to which the level of community welfare is obtained by MSME pottery artisans in Kasongan Tourism Village. This study uses the welfare theory approach and compliance theory to identify the influence of intrinsic motivation and extrinsic motivation on community welfare mediated by tax compliance. Tax compliance acts as a mediating variable that links intrinsic motivation and extrinsic motivation to community welfare. The research method used is a quantitative approach, and the research sample consisted of 65 MSME pottery artisans selected through purposive sampling. The results show that intrinsic motivation has a significant positive effect on tax compliance, while extrinsic motivation has no significant effect on tax compliance. Tax compliance has a positive and significant effect on community welfare. Furthermore, tax compliance mediates the relationship between intrinsic motivation and community welfare but does not mediate the relationship between extrinsic motivation and community welfare. This study implies that intrinsic motivation is more effective in encouraging tax compliance and improving community welfare than extrinsic motivation, which needs to be supported by more appropriate policies to have a significant effect.